The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s11201-005-9000-5
|View full text |Cite
|
Sign up to set email alerts
|

Bromination of octaphenylsilsesquioxane

Abstract: The bromination and characterization of octaphenylsilsesquioxane is reported. The reaction is successful with a variety of methods, including microwave assisted synthesis. The analysis of the obtained product mix was carried out with a combination of high performance liquid chromatography and matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF-MS). The analysis indicates that the bromination leads to multiple bromines per octaphenylsilsesquioxane molecule with a distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Thus, LAs (e.g., iron or iron trichloride) will complex with Br 2 , generating cationic Br + equivalents that react readily with aromatic groups. , Iron-catalyzed bromination of [PhSiO 1.5 ] 8 or OPS was described by Laine et al (reaction ), by He et al, and by Brick et al The bromination of OPS by IBr was reported by Erben et al …”
Section: Halogenationmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, LAs (e.g., iron or iron trichloride) will complex with Br 2 , generating cationic Br + equivalents that react readily with aromatic groups. , Iron-catalyzed bromination of [PhSiO 1.5 ] 8 or OPS was described by Laine et al (reaction ), by He et al, and by Brick et al The bromination of OPS by IBr was reported by Erben et al …”
Section: Halogenationmentioning
confidence: 98%
“…The addition of the FeBr 3 catalyst after an initial stage of bromination without catalyst increases the degree of bromination beyond 16, reaction , providing highly insoluble white powders. Attempts to increase the degree of bromination to 24 led to significant Si−C cleavage as a side reaction, leaving a silanol functionalized corner, as detected in the crude reaction products by MALDI-TOF . It appears that the tribrominated corners are readily cleavedunder the highly acidic (due to HBr produced), oxidizing (due to excess Br 2 ) conditions.…”
Section: Halogenationmentioning
confidence: 99%
“…The general mechanism involves Br 2 coordination with the Lewis acid to generate species that behave like Br + that serve as the electrophilic intermediate that attacks aromatic groups. 38,39 Iron and iron trichloride catalyzed bromination of OPS was explored by Brick et al 23 and He et al 34 The bromination of OPS by IBr was reported by Erben et al 40 These studies gave products that were relatively disordered with respect to substitution patterns and number, in part because of the insolubility of OPS, which leads to extended bromination of the first brominated species as they become more soluble with increasing bromination. However, following our success with iodination, 36,37 we concluded it might be possible to more selectively brominate OPS.…”
Section: Octabromination Of Opsmentioning
confidence: 99%
“…The most common of these reactions are nitration 76,77 followed by reduction to an amino group, as well as halogenation. [78][79][80][81] The feasibility of performing this reaction is rather unusual. This is due to the fact that reactions of this kind usually result in the electrophilic substitution of silicon at the ipso position of the phenyl ring.…”
Section: Polyhedral Polyphenylsilsesquioxanesmentioning
confidence: 99%